ANALISIS IMLPIKATUR PERCAKAPAN PADA FILM ANTARES DALAM KAJIAN PRAGMATIK - Hidayat Ali Haromaini; Emy Rista Kusuma (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
In linguistics, the only aspect that discusses human language is called pragmatic studies. The meaning contained in an utterance in a pragmatic context is called implicature. Impilkature has become part of the conversational tools in communication. With this research, the author wants to know the implications of conversations in the film Antares. The author also uses a qualitative descriptive research method to determine the communication used in the film Antares. The results of the research show that conversational implicatures referring to Grice's theory can be applied in the use of implicatures in a film. The results of this research discuss the implications of general, specific and scaled conversations. Based on research findings, it can be concluded that implicatures often occur in the conversation process between speech partners and speakers, even if only in short sentences. Keywords: Linguistics, conversational implicature, pragmatics, Antares film.